Characterizing Drought Tolerance in Wheat Genotypes for Yield Associated Traits Under Different Water Stress Conditions - Shar, Piar Ali; Tahir, Muhammad Younas; Mastoi, Abdul Hafeez; Jamali, Kamran Hashim; Zarnaz; Naz, Nawal; Soomro, Farheen Deeba; Kaleri, Asif Ali; Soomro, Ayaz Ali; Mirbahar, Saddam Hussain (Journal of Agriculture and Biology, 2025)
For agriculture to improve crop performance, drought resistance was identified as a crucial breeding goal. During the Rabi season, this research evaluated six F2 segregating wheat progenies for grain production and related traits in both normal and water-stressed conditions. The plants had to respond to three different water treatments: T1 included regular irrigations, T2 involved one irrigation that escaped during the tillering stage, and T3 involved one irrigation that escaped during the booting stage. The variance analysis of traits such as tiller number m-2, panicle length (cm), grain yield per plant (g), harvest index, and osmotic potential (-MPa) of the six F2 segregating populations and their parent wheat varieties was significant (P≤0.05). Plant height (cm), number of spikelets (number per spike), number of grains (number per spike), thousand-grain weight (g), biological yield (kg ha⁻¹), and grain yield (kg ha⁻¹) are significant at P≤0.01. The T2 and T3 offspring of TD-1×Imdad, Sarsabz×Khirman, and Kiran-95×Khirman showed higher plant height, tiller number, spikelet number, panicle number, biological yield, yield kgha⁻¹, thousand-grain weight, and harvest index. Hybrids TD-1 × Imdad, TJ-83 × Khirman, Sarsabz × TJ-83, and Sarsabz × Khirman showed excellent performance under stress during the tillering stage, with Sarsabz × TJ-83 showing high grain production per plant. The total performance of the F2 progenies might be more favorable for selection under water stress conditions at various growth stages.
Keywords: Drought tolerance; grain yield; morphological traits; physiological traits; wheat